Tingkat Kepuasan Mahasiswa Terhadap Kinerja Proses Belajar Mengajar (PBM) Dosen - S Paly, Muhammad Basir (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
This study aims to determine the level of studetsâs satisfaction of the lecturer PBM performance. Carried out on April-August 2014 at Department of the animal science of Science and Technology Faculty UIN Alauddin Makassar. Factors and indicators of performance refers to the quality manual UIN Alauddin Makassar and Semarang State University (UNNES). A total of 60 samples have been observed. Using survey methods through observation and interviews with a list of questions. Measurement of satisfaction using a scale-linkert with four scales; not-satisfied, less-satisfied, satisfied, and very satisfied. The results showed that the studetsâs satisfaction level of the lecturer PBM performance are still dominant among scale